Detección de casos de Tuberculosis en escolares del Colegio Nacional «Jorge Basadre Grohmanm» del P.J. «El Independiente» - El Agustino-Lima, Perú - Rumiche B., Jesús (2003)
The objectives of the present investigation were to deted cases of pulmonary tuberculosis and to determine the prevalence rate between subjects: 776 students with ages between 5 and 18 years old, of both genders. We divided them in two groups: A) to 193 boys up to 7 years old,who were applied the PPD test. If the papule were greater or equal to of 10 mm. in diameter, the students were submitted to a radiological examination and sputum test. Positive casespassed a clinical examination. B) Students that were older than 7 years (n=573), were applied an epidemiological survey. The positive ánswers to cough for more than 15 days, fever, sweat, loss weight or being in clase contact with sick people of TBC, were categorized as a respiratory symptomatic ethiology ; the confirmation was made using baciloscopy technique. The diagnosed cases as positive were incorporated to the Health Department National Program of Tuberculosis Control. At the same time, it was carried out a study of socio economica1 conditions of the community; 9 cases were detected (4 males and 5 females) with ages between 6 and 14 years old that represents the prevalence rate of 1,15% making the study group, a population at higher risk.Between the major prevalent socio economical conditions we have: lack of basic services, 70% of the population in working age is unemployed or sub employed and ingest diets with inadequated protein content.The impact of this study is the evidence of a problem, where many sectors oí society publish TBC as a controlled disease but is impossible ta affirm such statement due to an increase of drug resistence of the bacteria.